MENINGKATKAN DISIPLIN ANAK USIA DINI MELALUI PEMBERIAN REWARD - madiyanah, ayuk nur; Farihah, Himmatul (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Preliminary observations show that learning at TK Dharma Wanita Siwalan Unity in Panceng sub-district, Gresik Regency is lacking in discipline in discipline. Various things that cause this, the lack of orderly regulations that apply at the institution, the lack of habituation of children so that the lack of discipline, and lack of support from parents. Out of 16 children, only 3 children are disciplined, some others still need guidance from the teacher. This study aims to: 1) describe the implementation of the provision of rewards in improving discipline in group B children in TK Dharma Wanita Unity Siwalan Panceng district Gresik district, 2) Explain the results of increased discipline of children through giving rewards to group B in Dharma Wanita Unity Siwalan Unity in Panceng district Gresik Regency. The Kemmis and Mc Taggart models used in this study were implemented through two action cycles. the initial discipline was developed in this study: 1) Arrival of children to school, 2) Ordering neatly and orderly into the classroom, 3) Uniformly neat according to school attributes. The results showed that by giving rewards to strive for discipline of children in the first cycle increased by 18.8% to 37.5%, and in the second cycle increased again by 37.5% to 81.3%. From the overall increase in numbers before the action until the beginning of the second cycle 62.5%.